Factors facilitating and hindering volunteering practices among ethnic-racial minority immigrants on the US-Mexico border. Issue 1 (2nd January 2022) - Paat, Yok-Fong
ABSTRACT: Using purposive sampling and in-depth interviews of 40 ethnic-racial minority immigrants (first-, 1.5-, and second- generations) on the US-Mexico border, this study examined factors that facilitated and hindered decisions to volunteer. Overall, analyses based on the Grounded Theory Method indicated that the participants' proclivity to volunteer was driven by multifaceted factors related to the availability of their personal resources, altruistic concerns over the welfare of the disadvantaged, cost-benefit analyses that factored opportunity cost in decision-making, self-interest, and personal benefits accrued. Specifically, volunteering could be used as a venue to foster professional career development, attain personal growth, reap emotional benefits, and fulfil altruistic callings. Factors that deterred the participants from volunteering consisted of value clashes with the agency management, personality conflicts with other volunteers, challenges confronted in working with difficult client populations, and time constraints. This study also supported the resource perspective where participants with more personal resources such as time, network, knowledge, values, skill sets, and expertise were able to volunteer in a wider variety of capacities. Study findings can be used to promote a culture of diversity and inclusion in volunteering, remove barriers that hinder involvement, and encourage contribution from this growing segment of the U.S. population.